STOP-Bang Criteria as a Difficult Airway Predictor in Surgical Patients at a Primary Referral Hospital in North Sumatra - Ikrar Rananta Simanjuntak; Andriamuri Primaputra Lubis; Ade Winata; Arlinda Sari Wahyuni (Talenta Publisher, 2026)
Introduction: Obstructive sleep apnea (OSA) is a sleep disorder associated with snoring, morning drowsiness, and hypoxemia, leading to an increased risk of difficult airway management. Polysomnography (PSG) is the gold standard for diagnosing OSA, but its high cost and limited accessibility necessitate alternative screening methods, such as the STOP-BANG questionnaire. Objective: This study aimed to evaluate the relationship between STOP-BANG scores and difficult airway conditions in surgical patients. Methods: A cross-sectional study was conducted at H. Adam Malik Hospital involving 110 surgical patients. Demographic and clinical data, including body mass index (BMI) and neck circumference, were collected. STOP-Bang scores were assessed preoperatively, and difficult airway conditions were documented. Results: The average BMI of the participants was 25.03 ± 2.62 kg/m², and the mean neck circumference was 27.83 ± 3.91 cm. A total of 81 patients reported a history of hypertension, a comorbidity frequently associated with OSA. Statistical analysis indicated that higher STOP-BANG scores were significantly correlated with a greater incidence of difficult airway conditions (p = 0.015). Conclusions: This study demonstrates that the STOP-BANG questionnaire has potential as a practical and accessible predictive tool for identifying patients at risk of difficult airway management related to OSA.